(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2014)
The current research examines the mediating role of sense of coherence between social support and outcomes including well-being and stress in collectivistic (Pakistan) and individualistic culture (Germany). Sample comprises of university students (N = 200) further equally divided in individualistic and collectivistic culture. Hierarchical regression is applied for data analysis. The hypotheses are confirmed by the findings. Sense of coherence partially mediated between social support and well-being in collectivistic culture, individualistic culture and overall sample. Similarly, sense of coherence partially mediated between social support and stress among students. The current investigation is an important addition in the literature on the theory of sense of coherence. The direct paths of sense of coherence and outcomes were well-established in the past literature; however, the present study contributes to the theory by suggesting an indirect path to well-being and stress.